Aluminum alloys, aluminum alloy wires, aluminum alloy members, and bolts
Optimized aluminum alloys with specific compositions achieve high strength and plastic workability, addressing the need for advanced materials for structural members and bolts.
Patent Information
- Application Number
- JP2021574691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-01-21
AI Technical Summary
There is a need for aluminum alloys with higher strength, particularly for structural members and bolts, which also maintain excellent plastic workability during manufacturing processes.
The development of aluminum alloys with specific compositions, including Si, Mg, Fe, Cu, Mn, Ni, Sn, and Cr, which are optimized to achieve high tensile strength, elongation, and resistance through precipitation hardening and solid solution strengthening, while maintaining good plastic workability.
The resulting aluminum alloys exhibit tensile strengths of 450 MPa or higher, elongation at break of 5% or more, and 0.2% strength of 390 MPa or higher, making them suitable for high-strength structural members and bolts with improved manufacturing efficiency.
Smart Images

Figure 0007658921000005 
Figure 0007658921000006 
Figure 0007658921000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an aluminum alloy, an aluminum alloy wire, an aluminum alloy member, and a bolt. This application claims priority based on Japanese Patent Application No. 2020-014172 filed on January 30, 2020, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0002] Patent Document 1 discloses an aluminum alloy having a tensile strength equal to or greater than that of an aluminum alloy having JIS alloy number A6056. Hereinafter, the aluminum alloy described in Patent Document 1 will be referred to as a conventional aluminum alloy. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-166480 A Summary of the Invention
[0004] The aluminum alloy of the present disclosure has a composition containing 1.0 mass% or more and 1.8 mass% or less of Si, 0.5 mass% or more and 1.2 mass% or less of Mg, 0.3 mass% or more and 0.8 mass% or less of Fe, 0.1 mass% or more and 0.4 mass% or less of Cu, 0.2 mass% or more and 0.5 mass% or less of Mn, 0 mass% or more and 0.3 mass% or less of Cr, and at least one of 0.005 mass% or more and 0.6 mass% or less of Ni and 0.005 mass% or more and 0.6 mass% or less of Sn, with the remainder being Al and unavoidable impurities.
[0005] The aluminum alloy wire of the present disclosure is made of the aluminum alloy of the present disclosure.
[0006] The aluminum alloy member of the present disclosure is made of the aluminum alloy of the present disclosure and has a tensile strength of 450 MPa or more.
[0007] The bolt of the present disclosure is made of the aluminum alloy of the present disclosure and has a tensile strength of 450 MPa or more, a fracture elongation of 5% or more, and a 0.2% yield strength of 390 MPa or more. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view showing an aluminum alloy wire according to an embodiment. [Diagram 2] FIG. 2 is a perspective view showing the bolt of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Problem that this disclosure aims to solve] Higher strength aluminum alloys are desired.
[0010] 6000 series alloys such as JIS alloy number A6056 have high strength due to heat treatment such as T6 treatment. 6000 series alloys are high strength alloys among the types of aluminum alloys. However, further improvement in strength is desired for aluminum alloys that constitute structural members, etc.
[0011] In the process of manufacturing structural members, etc., aluminum alloys are usually subjected to not only the above-mentioned heat treatment but also various plastic working processes, such as rolling, wire drawing, forging, etc. Therefore, it is preferable for the aluminum alloy to have high strength after heat treatment and excellent plastic workability during the manufacturing process.
[0012] Therefore, one object of the present disclosure is to provide an aluminum alloy suitable for use as a material for a high-strength aluminum alloy member. Another object of the present disclosure is to provide an aluminum alloy wire suitable for use as a material for a high-strength aluminum alloy member. Yet another object of the present disclosure is to provide a high-strength aluminum alloy member and a high-strength bolt.
[0013] [Effects of this disclosure] The aluminum alloy and aluminum alloy wire according to the present disclosure are suitable as materials for high-strength aluminum alloy members. The aluminum alloy member and the bolt according to the present disclosure have high strength.
[0014] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) An aluminum alloy according to one embodiment of the present disclosure has a composition including 1.0% by mass or more and 1.8% by mass or less of Si, 0.5% by mass or more and 1.2% by mass or less of Mg, 0.3% by mass or more and 0.8% by mass or less of Fe, 0.1% by mass or more and 0.4% by mass or less of Cu, 0.2% by mass or more and 0.5% by mass or less of Mn, 0% by mass or more and 0.3% by mass or less of Cr, and at least one of 0.005% by mass or more and 0.6% by mass or less of Ni and 0.005% by mass or more and 0.6% by mass or less of Sn, with the remainder being Al and unavoidable impurities.
[0015] As described later, Ni and Sn are considered to contribute to the effect of improving strength by dispersion strengthening. The aluminum alloy of the present disclosure contains one or both of Ni and Sn, unlike the conventional aluminum alloy described above. Therefore, the aluminum alloy of the present disclosure can form an aluminum alloy member having higher strength than an aluminum alloy member made of the conventional aluminum alloy described above.
[0016] Furthermore, the aluminum alloy of the present disclosure has excellent plastic workability in the manufacturing process of aluminum alloy members, making it suitable as a material for high-strength aluminum alloy members.
[0017] (2) An example of the aluminum alloy of the present disclosure includes an embodiment in which the Si content exceeds 1.2 mass % and the Mg content exceeds 0.8 mass %.
[0018] In the above embodiment, Mg2Si, which functions as a dispersion strengthener, is easily precipitated by aging treatment, and therefore the above embodiment can provide an aluminum alloy member with higher strength.
[0019] (3) An example of the aluminum alloy of the present disclosure includes an embodiment containing both the Ni and the Sn.
[0020] In the above embodiment, the effects of both Ni and Sn make it possible to form an aluminum alloy member having a higher strength.
[0021] (4) An example of an aluminum alloy according to the present disclosure has a tensile strength of 450 MPa or more after being subjected to a solution treatment and an aging treatment in that order, in which the solution treatment is performed at a temperature selected from the range of 545°C or more and 575°C or less, the solution treatment is performed for a time period selected from the range of 30 minutes or more and 60 minutes or less, the aging treatment is performed at a temperature selected from the range of 160°C or more and 180°C or less, and the aging treatment is performed for a time period selected from the range of 5 hours or more and 35 hours or less.
[0022] The above embodiment can provide an aluminum alloy part having a higher strength than the aluminum alloy part made of the above-mentioned conventional aluminum alloy.
[0023] (5) An example of the aluminum alloy of (4) above is one having a fracture elongation of 5% or more after the solution treatment and the aging treatment are carried out in sequence.
[0024] The above-mentioned embodiment can provide an aluminum alloy member having high strength and high elongation. In addition, since the elongation is high after aging treatment, plastic working may be possible. In this case, the above-mentioned embodiment also provides excellent manufacturability of the aluminum alloy member.
[0025] (6) An example of the aluminum alloy of (4) or (5) above is one having a 0.2% yield strength of 390 MPa or more after the solution treatment and the aging treatment are carried out in that order.
[0026] The above embodiment can provide an aluminum alloy member having high strength and high yield strength.
[0027] (7) An aluminum alloy wire according to one embodiment of the present disclosure is made of any one of the aluminum alloys described above in (1) to (6).
[0028] The aluminum alloy wire of the present disclosure is suitable for aluminum alloy members including a linear portion, such as a material for a bolt, etc. By using the aluminum alloy wire of the present disclosure, an aluminum alloy member having higher strength than the aluminum alloy members made of the above-mentioned conventional aluminum alloys can be formed.
[0029] (8) An example of the aluminum alloy wire according to the present disclosure has a wire diameter of 3 mm or more and 15 mm or less.
[0030] The above embodiment is suitable for aluminum alloy members including a linear portion having a wire diameter within the above range, such as materials for bolts and the like.
[0031] (9) An aluminum alloy structural member according to one embodiment of the present disclosure is made of any one of the aluminum alloys described above in (1) to (6) and has a tensile strength of 450 MPa or more.
[0032] The aluminum alloy member according to the present disclosure has higher strength than the aluminum alloy members made of the above-mentioned conventional aluminum alloys, and can be used as a high-strength structural member, etc.
[0033] (10) An example of the aluminum alloy member of (9) above is one that satisfies at least one of the following requirements: breaking elongation of 5% or more; and 0.2% yield strength of 390 MPa or more.
[0034] The above-mentioned embodiment can be used as a structural member having high strength and at least one of high elongation and high yield strength.
[0035] (11) A bolt according to one embodiment of the present disclosure is made of any one of the aluminum alloys (1) to (6) above, and has a tensile strength of 450 MPa or more, a breaking elongation of 5% or more, and a 0.2% yield strength of 390 MPa or more.
[0036] The bolt of the present disclosure has higher strength, higher elongation, and higher yield strength than the bolts made of the above-mentioned conventional aluminum alloys. Such a bolt of the present disclosure can form a strong fastening structure. Furthermore, the bolt of the present disclosure can maintain a strong fastening state for a long period of time.
[0037] [Details of the embodiment of the present disclosure] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings as appropriate.
[0038] [Aluminum alloy] (composition) The aluminum alloy of the embodiment is an alloy mainly composed of Al (aluminum) and contains additive elements. Specifically, the aluminum alloy of the embodiment contains Si (silicon), Mg (magnesium), Fe (iron), Cu (copper), Mn (manganese), and at least one of Ni (nickel) and Sn (tin), with the balance being Al and unavoidable impurities. The aluminum alloy of the embodiment may further contain Cr (chromium) in addition to the additive elements described above. The content and effect of each added element will be explained below.
[0039] 〈Si〉 The Si content is 1.0 mass % or more and 1.8 mass % or less. Si strengthens the aluminum alloy mainly by precipitation hardening. More specifically, Si functions as a dispersion strengthener by being dispersed in the parent phase together with Mg as fine Mg2Si. Mg2Si is a precipitate formed when Si dissolved in Al by solution treatment combines with Mg by aging treatment, i.e., artificial aging. The remaining Si that does not constitute Mg2Si strengthens the aluminum alloy by dissolving in Al, precipitating as Si alone, or crystallizing in a dendrite shape as Si alone. The aforementioned remaining Si is sometimes called excess Si. The parent phase is mainly composed of Al.
[0040] When the Si content is 1.0 mass% or more, the effect of improving the strength by the above-mentioned strengthening can be obtained well. Although it depends on the Mg content, the higher the Si content, the more likely the Mg2Si content will increase by aging treatment. As a result, the strength is likely to be improved. From the viewpoint of improving the strength, the Si content may be more than 1.0 mass%, 1.1 mass% or more, or 1.15 mass% or more. If the Si content is more than 1.2 mass%, the strength is likely to be further increased.
[0041] When the Si content is 1.8% by mass or less, the precipitates and crystallized products containing Si are unlikely to become coarse. In addition, the excess Si is not too much. Therefore, the decrease in strength caused by the coarse precipitates and crystallized products and the excess Si is suppressed. In addition, the decrease in plastic workability is also suppressed. Note that the coarse precipitates and crystallized products become the starting point of cracks, and the strength is likely to decrease. In addition, when there is too much excess Si, simple Si segregates at the grain boundaries of the crystals of the parent phase. This segregated Si embrittles the grain boundaries, and the strength is likely to decrease. From the viewpoint of suppressing the decrease in strength, the Si content may be 1.7% by mass or less, or 1.6% by mass or less. When the Si content is 1.5% by mass or less, the strength is unlikely to decrease.
[0042] When the Si content is more than 1.0 mass % and not more than 1.7 mass %, or more than 1.2 mass % and not more than 1.5 mass %, the above-mentioned decrease in strength is suppressed, and the aluminum alloy is likely to have high strength.
[0043] <Mg> The Mg content is 0.5% by mass or more and 1.2% by mass or less. Mg strengthens the aluminum alloy by dissolving in Al, and also strengthens the aluminum alloy by precipitation hardening together with Si as described above.
[0044] When the Mg content is 0.5 mass% or more, the strength improving effect due to solid solution strengthening and precipitation hardening can be obtained well. The higher the Mg content, the easier it is to improve the strength. From the viewpoint of improving the strength, the Mg content may be 0.6 mass% or more, or 0.7 mass% or more. If the Mg content exceeds 0.8 mass%, the strength is likely to be further increased.
[0045] When the Mg content is 1.2% by mass or less, excess Si is reliably generated. Therefore, the strengthening effect due to excess Si is well obtained. As a result, the strength is likely to be high. Furthermore, the yield strength is also likely to be high. In addition, macrosegregation is unlikely to occur during casting. The resistance to stress corrosion cracking, the plastic workability, and the heat resistance are unlikely to decrease. Since these effects are well obtained, the Mg content may be 1.15% by mass or less, or 1.1% by mass or less. If the Mg content is 1.05% by mass or less, the above-mentioned effects are even more likely to be obtained.
[0046] When the Mg content is 0.6% by mass or more and 1.15% by mass or less, or more than 0.8% by mass or less and 1.05% by mass or less, the strength and yield strength are likely to be improved, and the resistance to stress corrosion cracking, plastic workability, and heat resistance are unlikely to be deteriorated.
[0047] <Si and Mg> In particular, when the Si content is more than 1.2 mass% and the Mg content is more than 0.8 mass%, as described above, a large amount of Mg2Si is likely to precipitate by aging treatment. Therefore, the strength is likely to be further increased. From the viewpoint of improving the strength, the Si content may be 1.3 mass% or more and the Mg content may be 0.9 mass% or more. Furthermore, the Si content may be 1.35 mass% or more and the Mg content may be 0.95 mass% or more.
[0048] <Fe> The Fe content is 0.3 mass % or more and 0.8 mass % or less. Fe strengthens aluminum alloys mainly by dissolving in Al. Fe also contributes to making the crystals of the aluminum alloy finer. If the crystals are finer, the following effects (a) to (d) can be obtained. In addition, Fe can be expected to have the effect of making the aluminum alloy more susceptible to work hardening. Work hardening tends to improve strength and yield strength. (a) Fine Mg2Si particles are easily dispersed uniformly in the matrix, which makes it easier to improve strength and yield strength. (b) The amount of grain boundaries in the crystals increases. If there are many grain boundaries, embrittlement caused by the segregation of Si at the grain boundaries tends to be relatively small. Therefore, the decrease in strength due to embrittlement at the grain boundaries is suppressed. (c) Heat resistance and corrosion resistance are easily improved. (d) It is easy to perform plastic processing.
[0049] When the Fe content is 0.3 mass% or more, the above-mentioned effects of solid solution strengthening, crystal refinement, etc. can be obtained well. As a result, Mg2Si is easily precipitated in the parent phase and is easily dispersed and present in the parent phase. Therefore, the strength improvement effect due to precipitation hardening is easily obtained. The higher the Fe content, the easier it is to improve the strength. From the viewpoint of improving the strength, the Fe content may be 0.35 mass% or more, or 0.4 mass% or more. If the Fe content is 0.45 mass% or more, the strength is easily further increased.
[0050] When the Fe content is 0.8% by mass or less, the content of crystallized products and precipitates consisting of compounds containing Al and Fe is likely to be small. Therefore, the deterioration of plastic workability caused by the above-mentioned compounds is suppressed. From this point of view, it is easy to manufacture the aluminum alloy member. From the viewpoint of ensuring good plastic workability, the Fe content may be 0.7% by mass or less, or 0.6% by mass or less. When the Fe content is 0.55% by mass or less, good plastic workability is obtained.
[0051] If the Fe content is 0.35 mass % or more and 0.7 mass % or less, or 0.45 mass % or more and 0.55 mass % or less, the strength is likely to be further increased and good plastic workability is obtained.
[0052] <Cu> The Cu content is 0.1 mass % or more and 0.4 mass % or less. Cu mainly contributes to suppressing the adverse effects of Si segregated at the grain boundaries of the crystals of the parent phase. In detail, Cu forms precipitates with Si segregated at the grain boundaries through solution treatment and aging treatment. These precipitates are compounds that match the atomic arrangement of Al constituting the parent phase. Therefore, the above precipitates are unlikely to adversely affect the grain boundaries. The embrittlement of the grain boundaries caused by the segregated Si is suppressed, thereby suppressing the decrease in strength.
[0053] When the Cu content is 0.1 mass% or more, the embrittlement of the grain boundaries is suppressed. The higher the Cu content, the easier it is to suppress the decrease in strength due to the embrittlement of the grain boundaries. From the viewpoint of suppressing the decrease in strength, the Cu content may be 0.15 mass% or more, or 0.2 mass% or more. When the Cu content is 0.25 mass% or more, the decrease in strength is unlikely to occur.
[0054] By setting the Cu content to 0.4 mass% or less, the formation of a low melting point phase containing Cu is suppressed. As a result, the deterioration of corrosion resistance and heat resistance is suppressed. From the viewpoint of ensuring good corrosion resistance and heat resistance, the Cu content may be 0.38 mass% or less, or 0.36 mass% or less. If the Cu content is 0.35 mass% or less, good heat resistance and good corrosion resistance are easily obtained.
[0055] If the Cu content is 0.15 mass % or more and 0.38 mass % or less, or 0.25 mass % or more and 0.35 mass % or less, the above-mentioned decrease in strength is easily suppressed, and good heat resistance and corrosion resistance are obtained.
[0056] The Mn content is 0.2 mass % or more and 0.5 mass % or less. A portion of Mn strengthens the aluminum alloy by dissolving in Al. The remainder of Mn contributes to making the crystals of the aluminum alloy finer. More specifically, Mn forms a compound with Al. This compound prevents the crystals from becoming coarse. If the crystals are fine, the above-mentioned effects (a) to (d) can be obtained. Furthermore, Mn contributes to crystallizing the above-mentioned compound containing Al and Fe in a spherical shape. If the crystals are spherical, they are less likely to adversely affect the plastic workability. From this point of view, Mn contributes to improving the plastic workability.
[0057] When the Mn content is 0.2 mass% or more, the above-mentioned effects of solid solution strengthening, crystal refinement, spheroidization of crystallized particles, etc. can be satisfactorily obtained. The higher the Mn content, the easier it is to obtain these effects. From the viewpoint of improving strength, etc., the Mn content may be 0.22 mass% or more, or 0.24 mass% or more. When the Mn content is 0.25 mass% or more, the above-mentioned effects can be satisfactorily obtained.
[0058] When the Mn content is 0.5 mass% or less, the crystallized particles and precipitates made of the compound containing Al and Mn are unlikely to become coarse. Therefore, the decrease in strength and the decrease in plastic workability caused by the coarse crystallized particles and precipitates are suppressed. Furthermore, when the Mn content is 0.5 mass% or less, the solidus temperature of the molten aluminum alloy is not too high. From this point of view, the pouring temperature is not too high. Therefore, the aluminum alloy member can be easily manufactured. From the viewpoint of suppressing the decrease in strength and improving the manufacturability, the Mn content may be 0.45 mass% or less, or 0.4 mass% or less. When the Mn content is 0.35 mass% or less, the decrease in strength is unlikely to occur. Furthermore, the pouring temperature is not too high.
[0059] When the Mn content is 0.22% by mass or more and 0.45% by mass or less, or 0.25% by mass or more and 0.35% by mass or less, the above-mentioned effects of solid solution strengthening, crystal refinement, etc. are satisfactorily obtained. In addition, a decrease in strength is unlikely to occur. The casting temperature does not become too high.
[0060] <Cr> The Cr content is from 0% by mass to 0.3% by mass. When the Cr content is 0 mass%, i.e., when Cr is not contained, the total content of the additive elements is small. Therefore, the deterioration of the plastic workability caused by the total content of the additive elements being large is suppressed. In addition, the casting temperature does not become too high. From these points, it is easy to manufacture the aluminum alloy part.
[0061] When the Cr content is more than 0% by mass, that is, when Cr is contained, Cr forms a compound containing Al. This compound containing Al and Cr contributes to making the crystals of the aluminum alloy finer, similar to Mn. Cr also has the effect of improving heat resistance and corrosion resistance. From the viewpoint of improving strength by making the crystals finer, and improving heat resistance and corrosion resistance, the Cr content is, for example, 0.005% by mass or more, 0.01% by mass or more.
[0062] By setting the Cr content to 0.3% by mass or less, the crystallized products and precipitates of the above-mentioned compounds containing Al and Cr are unlikely to become coarse, as in the case of Mn. Also, the casting temperature does not become too high. From the viewpoint of suppressing the decrease in strength and improving manufacturability, the Cr content may be 0.2% by mass or less, 0.1% by mass or less, or 0.05% by mass or less.
[0063] When the Cr content is 0.005% by mass or more and 0.2% by mass or less, or 0.01% by mass or more and 0.05% by mass or less, the above-mentioned effects of making the crystal fine can be satisfactorily obtained. In addition, the strength is unlikely to decrease. The casting temperature does not become too high.
[0064] <Other elements> The aluminum alloy of the embodiment may further contain Sr (strontium) in addition to the above-mentioned additive elements. Sr has the effect of making the crystals of the cast material finer. In particular, when Sr is contained in the presence of Si, the size of crystallized particles of simple Si can be reduced. Therefore, the plastic workability such as rolling is improved. The Sr content may be, for example, 0.005% by mass or more and 0.05% by mass or less. From the viewpoint of making the cast material finer, the Sr content may be 0.005% by mass or more and 0.03% by mass or less.
[0065] 〈Ni〉 The Ni content is 0.005 mass % or more and 0.6 mass % or less. Ni contributes to finely precipitating the above-mentioned Mg2Si. Ni also contributes to making the crystals of the aluminum alloy fine. If both Mg2Si and the crystals are fine, it is easy to obtain a structure in which Mg2Si is dispersed in the parent phase and in which the number of Mg2Si present per unit area in the aluminum alloy is large. In such a structure, the effect of improving the strength by precipitation hardening is well obtained. Therefore, the strength is easily improved.
[0066] The Ni content of 0.005% by mass or more can provide the above-mentioned effect of improving strength. When the Ni content is 0.008% by mass or more, or 0.01% by mass or more, the strength is likely to be higher. When the Ni content is 0.015% by mass or more, the strength is likely to be further increased.
[0067] When the Ni content is 0.6 mass% or less, the crystallized particles and precipitates made of a compound containing Al and Ni are unlikely to become coarse. Therefore, the decrease in strength and the decrease in plastic workability caused by the coarse crystallized particles and precipitates are suppressed. From the viewpoint of suppressing the decrease in strength, the Ni content may be 0.5 mass% or less, or 0.4 mass% or less. When the Ni content is 0.3 mass% or less, the decrease in strength is unlikely to occur.
[0068] If the Ni content is 0.008 mass % or more and 0.5 mass % or less, or 0.015 mass % or more and 0.3 mass % or less, the effect of improving the strength can be satisfactorily obtained.
[0069] When the Si content exceeds 1.2 mass% and the Mg content exceeds 0.8 mass%, if the Ni content is 0.01 mass% or more and 0.5 mass% or less, or 0.03 mass% or more and 0.3 mass% or less, a good strength improving effect can be obtained.
[0070] 〈Sn〉 The Sn content is 0.005 mass % or more and 0.6 mass % or less. Sn contributes to retarding natural aging and accelerating artificial aging. That is, Sn accelerates the formation of Mg2Si during aging treatment. This acceleration is believed to occur as follows. Sn traps vacancies, which are atomic level defects in Al. Sn also traps Mg. By including Sn, more pairs of the vacancies and Mg are formed after solution treatment compared to the above-mentioned conventional aluminum alloys that do not include Sn. The diffusion of solute atoms occurs through the vacancies. Therefore, when there are many pairs of the vacancies and Mg, a lot of Mg2Si is formed when Mg reacts with Si in Al. Since Mg2Si is well formed, the strength is improved.
[0071] The Sn content of 0.005% by mass or more can provide the above-mentioned strength improvement effect. When the Sn content is 0.008% by mass or more, or 0.01% by mass or more, the strength is likely to be higher. When the Sn content is 0.015% by mass or more, the strength is likely to be further increased. In addition, Sn is considered to be easier to improve the strength than Ni.
[0072] When the Sn content is 0.6 mass% or less, the formation of a low melting point phase containing Sn is suppressed. Here, in an aluminum alloy containing a low melting point phase containing Sn, partial melting occurs during solution treatment. Due to partial melting, large voids are generated inside the aluminum alloy. The large voids become the starting points of cracks, resulting in a decrease in strength. Since the low melting point phase is unlikely to be formed, a decrease in strength caused by the low melting point phase is suppressed. In addition, a decrease in corrosion resistance is suppressed. Since these effects are satisfactorily obtained, the Sn content may be 0.5 mass% or less, or 0.4 mass% or less. If the Sn content is 0.3 mass% or less, the above-mentioned effects are more easily obtained.
[0073] If the Sn content is 0.008 mass % or more and 0.5 mass % or less, or 0.015 mass % or more and 0.3 mass % or less, the effect of improving the strength can be satisfactorily obtained.
[0074] When the Si content exceeds 1.2 mass% and the Mg content exceeds 0.8 mass%, the Sn content of 0.01 mass% or more and 0.5 mass% or less, or 0.03 mass% or more and 0.3 mass% or less, can satisfactorily improve the strength.
[0075] <Ni and Sn> When the aluminum alloy of the embodiment contains both Ni and Sn, the strength is likely to be further increased due to the effects of both Ni and Sn. The contents of Ni and Sn may be selected from the above-mentioned ranges. In particular, when the contents of Ni and Sn are both 0.03 mass% or more and 0.5 mass% or less, or 0.04 mass% or more and 0.3 mass% or less, the effect of improving the strength is obtained well.
[0076] (organization) The aluminum alloy of the embodiment typically has a structure in which precipitates are dispersed in the parent phase. The precipitates are typically compounds such as Mg2Si. In addition to the precipitates, crystallized matter also exists in the parent phase as described above. The structure in which the precipitates are dispersed is typically obtained by subjecting the aluminum alloy to a solution treatment and an aging treatment.
[0077] In the manufacturing process of the aluminum alloy of the embodiment, it is not necessary to carry out the solution treatment and the aging treatment consecutively. The aging treatment may be carried out after the solution treatment.
[0078] When the aluminum alloy of the embodiment constitutes a material such as an aluminum alloy member of the embodiment or a bolt of the embodiment described later, typically, the aluminum alloy is not subjected to solution treatment or aging treatment. Therefore, the aluminum alloy of the embodiment has a cast structure or solidified structure obtained by solidifying a molten metal, a processed structure obtained by performing plastic processing, a softened structure obtained by performing softening treatment on a plastically processed material, etc. The cast structure, processed structure, softened structure, and structure after aging treatment can be distinguished by, for example, observing a cross section of the aluminum alloy with a transmission electron microscope (TEM). The structure can be distinguished by, for example, the presence or absence and size of Mg2Si. Specifically, the processed structure, softened structure, and structure after aging treatment contain Mg2Si. Furthermore, the structure after aging treatment contains Mg2Si on the order of several nanometers. However, the processed structure and softened structure do not contain Mg2Si on the order of several nanometers.
[0079] (mechanical properties) The aluminum alloy of the embodiment has a higher strength than JIS alloy number A6056 and the above-mentioned conventional aluminum alloys by being subjected to solution treatment and aging treatment. Quantitatively, an example of the aluminum alloy of the embodiment has a tensile strength of 450 MPa or more after being subjected to solution treatment and aging treatment in this order under the following conditions.
[0080] Another example of the aluminum alloy of the embodiment has a fracture elongation of 5% or more in addition to the above-mentioned tensile strength after being subjected to solution treatment and aging treatment in sequence under the following conditions. In still another example of the aluminum alloy of the embodiment, after being subjected to solution treatment and aging treatment in sequence under the following conditions, in addition to the above-mentioned tensile strength, it has a 0.2% yield strength of 390 MPa or more.
[0081] (Solution treatment conditions) The holding temperature is selected from the range of 545°C or more and 575°C or less. The retention time is selected from the range of 30 minutes to 60 minutes. (Conditions for aging treatment) The holding temperature is selected from the range of 160°C or higher and 180°C or lower. The retention time is selected from the range of 5 hours to 35 hours.
[0082] The above-mentioned solution treatment conditions and aging treatment conditions are those simulating the solution treatment and aging treatment performed during the manufacturing process. The above-mentioned conditions include a plurality of "combinations of temperature and time" selected from the range of holding temperature and the range of holding time. An example of the aluminum alloy of the embodiment has a tensile strength of 450 MPa or more for at least one combination. Another example of the aluminum alloy of the embodiment has at least one of a fracture elongation of 5% or more and a 0.2% proof stress of 390 MPa or more in addition to the above-mentioned tensile strength for at least one combination.
[0083] The aluminum alloy after the solution treatment and aging treatment under the above-mentioned conditions will be described below.
[0084] Tensile strength The aluminum alloy of the embodiment having a tensile strength of 450 MPa or more has a higher strength than the conventional aluminum alloys described above. From the viewpoint of improving the strength, the tensile strength is preferably 452 MPa or more, more preferably 455 MPa or more. Depending on the composition, the tensile strength is 460 MPa or more, 465 MPa or more, or 470 MPa or more.
[0085] There is no particular upper limit for the tensile strength. From the viewpoint of suppressing a decrease in elongation, the tensile strength is, for example, 550 MPa or less.
[0086] <Breaking elongation> An aluminum alloy having a fracture elongation of 5% or more according to the embodiment has high strength and high elongation. In addition, the high elongation may allow plastic processing after aging treatment. In this case, the aluminum alloy member can be easily manufactured. From the viewpoint of ensuring good elongation, the fracture elongation may be 8% or more, or 9% or more. Depending on the composition, the fracture elongation is 10% or more, 12% or more, 15% or more, or 16% or more.
[0087] There is no particular upper limit for the breaking elongation. From the viewpoint of suppressing a decrease in strength, the breaking elongation is, for example, 40% or less.
[0088] <0.2% yield strength> An aluminum alloy having a 0.2% yield strength of 390 MPa or more according to the embodiment has high strength and high yield strength. The high yield strength makes it difficult for stress to be relaxed, for example. Such an aluminum alloy is suitable as a material for structural members such as bolts. From the viewpoint of improving the yield strength, the 0.2% yield strength may be 395 MPa or more, 400 MPa or more, or 405 MPa or more. Depending on the composition, the 0.2% yield strength is 410 MPa or more.
[0089] There is no particular upper limit for the 0.2% yield strength. From the viewpoint of suppressing a decrease in elongation, the 0.2% yield strength is, for example, 490 MPa or less.
[0090] <Measurement method> The tensile strength, breaking elongation, and 0.2% yield strength are measured by conducting a tensile test in accordance with JIS Z 2241: 2011. Test pieces for measurement are prepared in accordance with JIS Z 2241: 2011 from the aluminum alloy that has been subjected to the above-mentioned solution treatment and aging treatment.
[0091] (Main Effects) Since the aluminum alloy of the embodiment has a specific composition containing at least one of Ni and Sn as described above, it can form a high-strength aluminum alloy member. This effect will be specifically described in the following test examples.
[0092] [Aluminum alloy components] The aluminum alloy of the embodiment is typically used as a material for forming various aluminum alloy members. A representative example of an aluminum alloy member made of the aluminum alloy of the embodiment is a plastically worked material that has been subjected to at least one type of plastic working. The plastically worked material is likely to have high strength due to work hardening, compared to an aluminum alloy that has not been subjected to plastic working, typically a cast material. In addition, the aluminum alloy of the embodiment has a composition that is excellent in plastic workability as described above. Therefore, the plastically worked material is easy to manufacture.
[0093] Specific examples of plastically processed materials include primary processed materials and secondary processed materials obtained by further processing the primary processed materials.
[0094] The primary processed material is obtained by subjecting a cast material, including a continuous cast material, to plastic processing. Specific examples include rolled materials, wire-drawn materials, forged materials, extruded materials, etc. The primary processed materials are typically used as materials when manufacturing secondary processed materials. The rolled materials include wire-shaped and plate-shaped materials. Wire-shaped rolled materials include relatively thick ones, i.e., rod-shaped ones. An example of the drawn wire material is an aluminum alloy wire of the embodiment described later.
[0095] The secondary processed material is typically the final product. In the manufacturing process of secondary processed materials, further processing applied to the primary processed materials includes plastic processing, surface treatment such as anodizing and polishing, cutting, etc. Secondary processed materials are used for various structural members such as automobile parts and bicycle parts. Examples of automobile parts include bolts and spool valves. In the manufacturing process of bolts, the drawn wire material, which is the primary processed material, is subjected to forging processing such as head processing and rolling. In the manufacturing process of spool valves, the drawn wire material is subjected to cutting. Examples of bicycle parts include cranks, etc. In the manufacturing process of cranks, the cast material is subjected to forging.
[0096] In the manufacturing process of the secondary processed material, solution treatment and aging treatment are performed at appropriate times, so that the secondary processed material has high tensile strength, as described below. Furthermore, the secondary processed material may have high strength and at least one of high elongation and high yield strength.
[0097] <Mechanical properties> The aluminum alloy member of the embodiment is made of the aluminum alloy of the embodiment and has a tensile strength of 450 MPa or more. If the tensile strength is 450 MPa or more, the aluminum alloy member of the embodiment has a higher strength than the aluminum alloy member made of the above-mentioned conventional aluminum alloy. Such an aluminum alloy member of the embodiment can be used as a high-strength structural member. The range of the tensile strength is the same as that in the above-mentioned item "Tensile strength".
[0098] An example of an aluminum alloy member according to an embodiment satisfies at least one of the following requirements in addition to the above-mentioned tensile strength: a breaking elongation of 5% or more and a 0.2% proof stress of 390 MPa or more. An aluminum alloy member according to an embodiment having a breaking elongation of 5% or more can be used as a high-strength and high-toughness structural member. An aluminum alloy member according to an embodiment having a 0.2% proof stress of 390 MPa or more can be used as a high-strength and high-proof stress structural member. If the proof stress is high, for example, stress is not easily relaxed. Therefore, a high-strength and high-proof stress structural member can be suitably used as a fastening member such as a bolt. The range of the breaking elongation and the range of the 0.2% proof stress are the same as those in the above-mentioned items <Breaking elongation> and <0.2% proof stress>.
[0099] If the aluminum alloy member of the embodiment has a tensile strength of 450 MPa or more, a breaking elongation of 5% or more, and a 0.2% yield strength of 390 MPa or more, it can be suitably used as a structural member with high strength, high toughness, and high yield strength. Note that a test piece for the tensile test may be prepared from the aluminum alloy member in accordance with JIS Z 2241:2011.
[0100] <Aluminum alloy wire> Hereinafter, an aluminum alloy wire according to an embodiment will be described with reference to FIG. The aluminum alloy wire 1 of the embodiment is made of the aluminum alloy of the embodiment. A representative example of the aluminum alloy wire 1 is the drawn wire material, which is the above-mentioned primary processed material. In this case, the aluminum alloy wire 1 is a secondary processed material, and can be used as a material for an aluminum alloy member including a linear portion, for example, a bolt material. Since the aluminum alloy wire 1 is made of the aluminum alloy of the embodiment, plastic processing such as forging can be easily performed in the manufacturing process of the secondary processed material, as described above.
[0101] The shape and size of the aluminum alloy wire 1 can be appropriately selected depending on the application and the like. Regarding the shape, the aluminum alloy wire 1 may be, for example, a round wire whose cross-sectional shape is a circle, a rectangular wire whose cross-sectional shape is a polygon such as a rectangle, or an irregularly shaped wire whose cross-sectional shape is an ellipse, etc. The cross section here is a cross section obtained by cutting the aluminum alloy wire 1 along a plane perpendicular to the axial direction of the aluminum alloy wire 1.
[0102] Regarding the size, the aluminum alloy wire 1 has a wire diameter D1 of, for example, 3 mm or more and 15 mm or less. If the wire diameter D1 is within the above range, the aluminum alloy wire 1 can be used, for example, as a material for bolts, a material for spool valves, etc. Furthermore, an aluminum alloy wire 1 having a wire diameter D1 of 13 mm or less, further 12 mm or less, is suitable as a material for bolts having a size suitable for fastening automobile parts, etc.
[0103] The wire diameter D1 here is measured as follows. A cross section of the aluminum alloy wire 1 is taken. In this cross section, the smallest circle that contains the contour line of the aluminum alloy wire 1 is taken. The wire diameter D1 is the diameter of this smallest circle. If the aluminum alloy wire 1 is a round wire, the outer diameter of the round wire corresponds to the wire diameter D1.
[0104] The length of the aluminum alloy wire 1 is not particularly limited. If the aluminum alloy wire 1 is the above-mentioned primary processed material, it has a length that can be wound into a coil, for example, a length of 3 m or more. If the aluminum alloy wire 1 is used as a material for the above-mentioned secondary processed material, it is typically cut to a predetermined length. The cut pieces are subjected to secondary processing.
[0105] In addition, when the aluminum alloy wire 1 is subjected to solution treatment and aging treatment in the manufacturing process, it has high strength as described above. Such an aluminum alloy wire 1 can be used as a high-strength wire. Furthermore, it may have high strength and at least one of high elongation and high yield strength. The ranges of the tensile strength, the range of the breaking elongation, and the range of the 0.2% yield strength of the aluminum alloy wire 1 are the same as those in the above-mentioned section on mechanical properties. A test piece for a tensile test may be prepared from the aluminum alloy wire 1 in accordance with JIS Z 2241:2011.
[0106] <bolt> The bolt of the embodiment will be described below with reference to FIG. 2 as needed. The bolt 10 of the embodiment is made of the aluminum alloy of the embodiment, and has a tensile strength of 450 MPa or more, a breaking elongation of 5% or more, and a 0.2% yield strength of 390 MPa or more. The bolt 10 of the embodiment has a higher strength than bolts made of the above-mentioned conventional aluminum alloys. Therefore, the bolt 10 can form a strong fastening structure. The bolt 10 of the embodiment also has high elongation and high yield strength. Therefore, the bolt 10 is not only not easily broken, but also not easily relaxed in stress. Therefore, the bolt 10 can maintain a strong fastening state for a long period of time.
[0107] Bolt 10 typically includes a head 11 and a shank 12. Shank 12 includes a threaded portion 13. Threaded portion 13 is provided in an area on the surface side of shank 12, ranging from the tip of shank 12 to a predetermined position on shank 12.
[0108] The bolt 10 can be manufactured using the aluminum alloy wire 1 of the embodiment, which is the above-mentioned primary processed material. The aluminum alloy wire 1 is cut to a predetermined length. The cut pieces are subjected to forging such as head processing and rolling processing. Furthermore, the bolt 10 is manufactured by performing solution treatment and aging treatment at an appropriate time.
[0109] The shape and size of the bolt 10 can be selected appropriately. Regarding the shape, FIG. 2 illustrates a hexagonal bolt whose head 11 is a hexagonal column, but this can be modified as appropriate. Regarding size, for example, for a hexagonal bolt, the "nominal thread diameter d" specified in JIS B 1180:2014 ranges from M2 to M12.
[0110] The tensile strength, breaking elongation, and 0.2% yield strength of the bolt 10 can be measured, for example, by a tensile test using the bolt 10 itself as a test piece in accordance with JIS B 1051:2000.
[0111] The tensile strength, breaking elongation, and 0.2% yield strength of the aluminum alloy itself constituting the bolt 10 can be measured by performing a tensile test in accordance with JIS Z 2241:2011. Here, as described above, in the manufacturing process of the bolt 10, forging is performed. The strength of the bolt 10 may be improved due to work hardening caused by the forging process. Therefore, when measuring the tensile strength and the like of the aluminum alloy itself, a test specimen is made from an internal region of the shaft portion 12 of the bolt 10 where the threaded portion 13 is not provided. In other words, this test specimen is made from a region that is not substantially work hardened by the forging process, or a region that is less affected by work hardening. Specifically, the test specimen can be made from the core portion 120 of the shaft portion 12 in which the surface side region including the threaded portion 13 is cut and removed.
[0112] The ranges of the tensile strength, the breaking elongation, and the 0.2% yield strength of the bolt 10 are the same as those in the above-mentioned sections "tensile strength", "breaking elongation", and "0.2% yield strength".
[0113] (Main Effects) The aluminum alloy member of the embodiment and the bolt 10 of the embodiment have a tensile strength of 450 MPa or more, which is high strength. The aluminum alloy wire 1 of the embodiment can be suitably used as a material for the high-strength aluminum alloy member and the bolt 10 described above, for example.
[0114] [Method of manufacturing aluminum alloys] The aluminum alloy of the embodiment can be classified according to the manufacturing process as a use form, and can be cast material, plastic processing material, heat treatment material, cutting processing material, surface treatment material, etc. As a basic manufacturing method for manufacturing these use forms, the manufacturing method described in Patent Document 1 can be used. That is, in the manufacture of the aluminum alloy of the embodiment, there is little or no significant change in the manufacturing process compared to the manufacturing method described in Patent Document 1. In this respect, the aluminum alloy of the embodiment is excellent in manufacturability. The manufacturing method will be briefly described below.
[0115] The casting material is produced through a first step of casting a molten aluminum alloy having the specific composition described above.
[0116] The plastically worked material is produced, for example, by subjecting at least a part of the above-mentioned cast material to one or more types of plastic working in a second step.
[0117] The heat-treated material is manufactured, for example, by subjecting the above-mentioned cast material or the above-mentioned plastically worked material to a third step of heat treatment. Examples of the heat treatment include solution treatment and aging treatment. The aluminum alloy member of the embodiment and the bolt 10 of the embodiment having a tensile strength of 450 MPa or more are examples of heat-treated materials. Therefore, in the manufacturing process of the aluminum alloy member and the bolt 10 of the embodiment, the heat treatment includes solution treatment and aging treatment. The aging treatment can be performed at any time after the solution treatment. Other heat treatments include softening treatment and the like.
[0118] The machined material and surface-treated material are produced, for example, by a fourth step in which the above-mentioned cast material, the above-mentioned plastically worked material, or the above-mentioned heat-treated material is machined and surface-treated.
[0119] Therefore, the aluminum alloy of the embodiment may be produced by a production method including the first step described above. Alternatively, the aluminum alloy of the embodiment may be produced by a production method including at least one of the second step, the third step, and the fourth step described above in addition to the first step. The production process may be selected according to the above-mentioned usage form. Each step will be explained below.
[0120] <First process: Casting> In the first step, various casting methods can be used. In particular, when a long continuous aluminum alloy wire or the like is to be produced, a continuous casting method can be suitably used.
[0121] The continuous casting method can solidify the molten metal at a faster solidification rate than billet casting. In other words, rapid solidification is possible. Rapid solidification makes it difficult for the above-mentioned crystallized products to become coarse. In addition, the crystals of the cast material tend to become fine.
[0122] If the amount of coarse crystallized matter is small, the additive elements are easily dissolved in Al during the solution treatment. As a result, Mg2Si is easily formed during the aging treatment performed after the solution treatment. In the aluminum alloy of the embodiment, Mg2Si is more easily formed due to the action of Sn as described above. In addition, in the aluminum alloy of the embodiment, Mg2Si is more easily precipitated finely due to the action of Ni as described above. If the cast material has a fine crystal structure, a fine crystal structure is more easily obtained even after casting. In the aluminum alloy of the embodiment, a fine crystal structure is more easily obtained due to the action of Fe, Mn, and optionally Cr as described above. If the parent phase has a fine crystal structure, fine Mg2Si is more easily dispersed uniformly in the parent phase. As a result, the effect of improving strength by precipitation hardening is obtained well.
[0123] In addition, in the continuous casting method, the crystals tend to be finer and the proportion of equiaxed crystals per unit cross-sectional area tends to be higher. Therefore, it is easy to perform plastic processing after casting. In addition, the plastic processed material obtained after plastic processing tends to have excellent surface properties. Furthermore, if the continuous cast material is used as a material for rolled materials, wire drawn materials, etc., rolled materials, wire drawn materials, etc. can be mass-produced.
[0124] The continuous casting method can be, for example, a known method such as a belt and wheel method or a Properti method. The solidification rate in continuous casting, i.e., the cooling rate of the molten metal, can be 1°C / sec or more. The faster the solidification rate, the easier it is to obtain the above-mentioned effects such as fine graining. The solidification rate may be 2°C / sec or more, 5°C / sec or more, 8°C / sec or more, or 10°C / sec or more. If the solidification rate of the entire molten metal is 1°C / sec or more, the entire molten metal is cooled uniformly, which is preferable. In this case, the components of the cast material tend to be uniform. Therefore, the homogenization process can be omitted. Note that, as long as the solidification rate is 1°C / sec or more, the casting method may be a method other than the continuous casting method.
[0125] <Second process: plastic processing> Examples of the plastic working applied to the cast material include rolling, wire drawing, forging, extrusion, etc. The plastic working can be hot, warm, or cold. One plastic working may include multiple passes.
[0126] <Third process: Heat treatment> The holding time in the heat treatment here does not include the temperature rise time. <Solution treatment> In the solution treatment, the holding temperature may be selected from 545° C. to 575° C. The holding time may be selected from 30 minutes to 60 minutes. The time required to raise the temperature to the holding temperature may be 60 minutes or less.
[0127] If the holding temperature is 545° C. or higher, the additive element is likely to dissolve in Al. From the viewpoint of promoting the dissolution, the holding temperature may be 550° C. or higher, 555° C. or higher, or 560° C. or higher. If the holding temperature is 575° C. or lower, the amount of Si segregated at the grain boundaries of the crystals is likely to be reduced. From the viewpoint of reducing the amount of segregated Si, the holding temperature may be 570° C. or lower.
[0128] If the holding time is 30 minutes or more, the additive element is likely to dissolve in Al. From the viewpoint of promoting the solid solution, the holding time may be 35 minutes or more, or 40 minutes or more. If the holding time is 60 minutes or less, the amount of Si segregated at the grain boundaries of the crystals is likely to be reduced. From the viewpoint of reducing the amount of segregated Si, the holding time may be 55 minutes or less, or even 50 minutes or less.
[0129] 《Statute of Limitations》 In the aging treatment, the holding temperature may be selected from the range of 160° C. to 180° C. The holding time may be selected from the range of 5 hours to 35 hours.
[0130] If the holding temperature is 160°C or higher, Mg2Si and the like will precipitate. As a result, the effect of improving strength due to precipitation hardening can be obtained. From the viewpoint of promoting precipitation, the holding temperature may be 165°C or higher. If the holding temperature is 180°C or less, the precipitates are less likely to become coarse. As a result, breakage caused by coarse precipitates is suppressed. From this point of view, the strength is likely to be high. From the viewpoint of suppressing the coarsening of precipitates, the holding temperature may be 175°C or less.
[0131] If the holding time is 5 hours or more, Mg2Si and the like are precipitated. As a result, the effect of improving the strength is obtained as described above. From the viewpoint of promoting the precipitation, the holding time may be 8 hours or more, or 10 hours or more. If the holding time is 35 hours or less, the precipitates are less likely to become coarse. As a result, the fracture is suppressed as described above. From the viewpoint of suppressing the coarsening of the precipitates, the holding time may be 30 hours or less. When the holding temperature is low within the above range, Mg2Si and the like are likely to precipitate if the holding time is long. When the holding temperature is high within the above range, the holding time may be short.
[0132] <Softening treatment> Other conditions for the softening treatment include, for example, a holding temperature selected from 250° C. or more and 450° C. or less, and a holding time selected from 0.5 hours or more and 40 hours or less.
[0133] <Method of manufacturing aluminum alloy wire> The aluminum alloy wire of the embodiment can be produced, for example, by the following production method, which includes the above-mentioned first step, the above-mentioned second step, and a third step of performing a softening treatment as a heat treatment on the plastically worked material produced in the above-mentioned second step.
[0134] In the first step, the casting can be mass-produced by using the continuous casting method as described above. In the second step, the plastic processing can be easily performed and a long drawn wire can be obtained. If necessary, the surface of the cast material can be cut before the second step.
[0135] The plastic working in the second step includes wire drawing. The plastic working in the second step may include rolling or swaging in addition to wire drawing. The rolling or swaging is typically performed in a hot or warm state. When the rolling is performed continuously with the casting, the rolled material can be mass-produced. In this case, for example, a Properti type continuous casting and rolling mill can be used. The wire drawing is typically performed in a cold state, and if necessary, a scalping process can be performed before the wire drawing.
[0136] The softening treatment in the third step is typically performed for the purpose of removing the strain introduced by the plastic working. The softening treatment can be performed, for example, (1) after rolling or swaging, i.e., before wiredrawing, (2) between passes when multiple passes of wiredrawing are performed, or (3) after the final pass. The softening treatment is performed at least at one of the above times. For the conditions of the softening treatment, please refer to the above section on "Softening Treatment".
[0137] <Method for manufacturing aluminum alloy member> The aluminum alloy member of the embodiment having the above-mentioned high tensile strength can be produced, for example, by the following first production method, second production method, or third production method.
[0138] The first manufacturing method includes the above-mentioned first step, the above-mentioned second step, and a third step of subjecting the plastically worked material manufactured in the above-mentioned second step to a heat treatment. The heat treatment in the third step includes a solution treatment and an aging treatment. The second manufacturing method includes the above-mentioned first step and a step of subjecting the cast material manufactured in the first step to a heat treatment, the heat treatment including a solution treatment and an aging treatment. The third production method is the first production method or the second production method, further comprising a step of performing plastic working after the aging treatment. For the conditions of the solution treatment and aging treatment, please refer to the above sections "Solution Treatment" and "Aging Treatment".
[0139] When the second step includes a plurality of types of plastic working, or when one plastic working includes a plurality of passes of plastic working, the solution treatment may be carried out between one plastic working and another, or between passes.
[0140] The aging treatment can be carried out at any time after the solution treatment. For example, the aging treatment may be carried out immediately after the solution treatment. Alternatively, processing such as plastic working and cutting may be carried out between the solution treatment and the aging treatment.
[0141] When the aluminum alloy member of the embodiment has a wire-shaped portion, the aluminum alloy wire of the embodiment can be used as the plastically worked material in place of the first step and the second step in the first manufacturing method.
[0142] <Bolt manufacturing method> The bolt of the embodiment having the above-mentioned high tensile strength can be manufactured, for example, by the following manufacturing method. This manufacturing method includes a step of cutting the aluminum alloy wire of the embodiment to a predetermined length, a step of performing plastic processing on the cut pieces, a step of performing solution treatment on the cut pieces or the plastic processing material, and a step of performing aging treatment after the solution treatment. The plastic processing here includes forging processing such as header processing and rolling processing. The aging treatment is performed, for example, after rolling processing.
[0143] [Test Example 1] The aluminum alloy wires having the compositions shown in Tables 1 to 4 were subjected to solution treatment and aging treatment in this order under the following conditions, and then their tensile strength (MPa), 0.2% yield strength (MPa), and fracture elongation (%) were measured. The measurement results are shown in Tables 1 to 4.
[0144] Sample Description Each sample shown in Tables 1 to 4 contains Si, Mg, Fe, Cu, and Mn as added elements. Some samples further contain Cr in addition to the above five elements. Or, some samples further contain Cr and Sr in addition to the above five elements. The content of each element is the amount (mass %) shown in Tables 1 to 4. In the composition of each sample shown in Tables 1 to 4, the balance is Al and unavoidable impurities. In Tables 1 to 4, a hyphen "-" indicates that no element is added.
[0145] 《Table 1 Sn addition》 Samples No. 1 to No. 8 shown in Table 1 contain Sn in addition to the above elements.
[0146] 《Table 2 Ni addition》 Samples No. 11 to No. 18 shown in Table 2 contain Ni in addition to the above elements.
[0147] Table 3: Ni and Sn addition Samples No. 21 to No. 32 shown in Table 3 contain both Ni and Sn in addition to the above elements.
[0148] Table 4 High Si and High Mg Samples No. 41 to No. 53 shown in Table 4 have a Si content of more than 1.2 mass % and a Mg content of more than 0.8 mass %. Samples No. 41 to No. 46 contain Sn in addition to the above elements. Samples No. 47 to No. 53 contain Ni in addition to the above elements.
[0149] Hereinafter, samples No. 1 to No. 53 containing at least one of Ni and Sn may be collectively referred to as a specific sample group.
[0150] Sample No. 101 Sample No. 101 shown in Tables 1 to 4 is a sample containing Si, Mg, Fe, Cu, Mn, and Cr as additive elements, but not containing Ni or Sn. In other words, sample No. 101 corresponds to the conventional aluminum alloy described above.
[0151] (Preparation of Aluminum Alloy Wire) The aluminum alloy wire was a drawn wire material having a wire diameter of 4.6 mm, and was prepared as follows. Pure aluminum is melted to produce molten metal. The additive elements are added to the molten metal so that the content of the additive elements becomes the amount (mass %) shown in Tables 1 to 4, and the molten metal is then held for a predetermined time. The molten aluminum alloy having the adjusted composition is appropriately subjected to treatment for removing hydrogen gas and foreign matter. The molten aluminum alloy is cast. The pouring temperature is 730℃. The solidification rate during casting is 1℃ / sec or more. The cast material is a round bar with a diameter of 30mmφ.
[0152] The surface of a 30 mm diameter cast material is machined to produce a 24 mm diameter round bar. The surface-cut round bar is warm swaged to produce a wire with a diameter of 10.3 mm. The heating temperature for swaging is 300°C. The swaged wire is cold drawn to produce a drawn wire with a diameter of 4.6 mm. Here, the wire before drawing, intermediate drawn wire with a diameter of 8.2 mm, and intermediate drawn wire with a diameter of 6.3 mm were each softened. The conditions for all three softening treatments were a holding temperature of 300°C and a holding time of 3 hours.
[0153] The composition of the obtained drawn wire material is the same as the composition shown in Tables 1 to 4. A known method can be used to analyze the composition of the drawn wire material. For example, an energy dispersive X-ray analyzer can be used.
[0154] <Heat treatment conditions> The conditions for solution treatment are a holding temperature of 560°C and a holding time of 45 minutes. After the holding time has elapsed, water quenching is performed. The heating time to the holding temperature is 45 minutes. The conditions of the aging treatment are a holding temperature of 160° C. and a holding time of 16 hours or 30 hours. In addition, no homogenization treatment was performed on each sample after casting and before the solution treatment.
[0155] Evaluation of mechanical properties Tensile strength (MPa), 0.2% yield strength (MPa), and breaking elongation (%) are measured by conducting a tensile test at room temperature in accordance with JIS Z 2241:2011. Test pieces are prepared from the above-mentioned drawn wire material with a wire diameter of 4.6 mm that has been subjected to the above-mentioned solution treatment and aging treatment.
[0156] [Table 1]
[0157] [Table 2]
[0158] [Table 3]
[0159] [Table 4]
[0160] As shown in Tables 1 to 4, it can be seen that the specific sample group made of an aluminum alloy containing at least one of Ni and Sn has a higher tensile strength than sample No. 101 which does not contain either Ni or Sn. Quantitatively, most of the specific sample group have a tensile strength of 450 MPa or more. Among the specific sample group, there are samples having a tensile strength of 460 MPa or more, and even 470 MPa or more. This shows that both Ni and Sn contribute to improving strength.
[0161] Furthermore, the specific sample group has a 0.2% yield strength of 390 MPa or more. Many of the samples in the specific sample group have a 0.2% yield strength of 400 MPa or more. Some samples in the specific sample group have a higher yield strength than sample No. 101. In particular, some samples in the specific sample group have a 0.2% yield strength of 410 MPa or more. From this, it is believed that both Ni and Sn also contribute to improving the yield strength.
[0162] Furthermore, the specific sample group has a breaking elongation of 5% or more. Many of the samples in the specific sample group have a breaking elongation of 10% or more. Some of the samples in the specific sample group have a higher elongation than sample No. 101. In particular, some of the samples in the specific sample group have a breaking elongation of 16% or more. From this, it is considered that both Ni and Sn also contribute to improving elongation.
[0163] Furthermore, among the specific sample group, there is a sample whose tensile strength, 0.2% yield strength, and fracture elongation are all higher than those of sample No. 101. This shows that an aluminum alloy containing at least one of Ni and Sn in addition to Si, Mg, Fe, Cu, and Mn can form an aluminum alloy member with high strength, high yield strength, and high toughness. It was also shown that an aluminum alloy containing at least one of Ni and Sn in addition to Si, Mg, Fe, Cu, and Mn, or containing Cr and Sr, can also form an aluminum alloy member with high strength, high yield strength, and high toughness.
[0164] Other findings from this test include: (1) Focus on Table 1. Here, it can be said that the tensile strength and 0.2% yield strength tend to be higher when the Sn content is in the range of 0.005 mass % or more and 0.30 mass % or less.
[0165] (2) Focus on Table 2. Here, it can be said that the tensile strength and 0.2% yield strength tend to be higher when the Ni content is in the range of more than 0.01 mass% and not more than 0.50 mass%.
[0166] (3) In Table 3, Table 1, and Table 2, samples with similar Sn and Ni contents are compared. For example, Sample No. 26 is compared with Samples No. 3 and No. 14. As a result, it can be said that samples containing both Ni and Sn tend to have higher tensile strength than samples containing Sn or Ni. Among the specific sample group shown in Table 3, many samples have tensile strength of 460 MPa or more. Here, when both Sn and Ni are contained, it can be said that it is preferable that the Sn content is 0.05 mass% or more and 0.20 mass% or less, and the Ni content is 0.05 mass% or more and less than 0.30 mass%.
[0167] (4) In Table 4, Table 1, and Table 2, samples with similar Sn and Ni contents are compared. For example, sample No. 43 is compared with sample No. 4. Also, for example, sample No. 48 is compared with sample No. 13. As a result, samples containing relatively large amounts of Si and Mg and Ni or Sn tend to have higher tensile strength than samples containing relatively small amounts of Si and Mg. Many of the samples in the specific sample group shown in Table 4 have tensile strengths of 460 MPa or more. From this, it can be said that containing large amounts of Si and Mg instead of both Ni and Sn contributes to improving strength.
[0168] The above test results show that the aluminum alloy having the above-mentioned specific composition containing at least one of Ni and Sn has a higher strength than conventional aluminum alloys by being subjected to solution treatment and aging treatment. In some cases, it has also been shown that one or both of the elongation and the yield strength are higher than conventional aluminum alloys. Such aluminum alloys are suitable for use as materials for structural members such as bolts.
[0169] The present invention is not limited to these examples, but is intended to include all modifications within the meaning and scope of the claims, as defined by the appended claims. For example, in Test Example 1, the type and content of the additive elements, the solution treatment conditions, the aging treatment conditions, the wire diameter, etc. can be appropriately modified. For example, in Test Example 1, the wire rod subjected to the cold wire drawing may be a continuously cast and rolled material. [Explanation of symbols]
[0170] 1. Aluminum alloy wire 10 bolt, 11 head, 12 shaft, 13 thread, 120 core D1 Wire diameter
Claims
1. 1.0% by mass or more and 1.8% by mass or less of Si; 0.8% by mass or more and 1.2% by mass or less of Mg; 0.5% by mass or more and 0.8% by mass or less of Fe; 0.1% by mass or more and 0.4% by mass or less of Cu; 0.2% by mass or more and 0.5% by mass or less of Mn; 0% by mass or more and 0.3% by mass or less of Cr; Contains at least one of 0.005% by mass to 0.6% by mass of Ni and 0.005% by mass to 0.6% by mass of Sn, The balance is composed of Al and inevitable impurities. Aluminum alloy.
2. The content of Si is more than 1.2 mass%, 2. The aluminum alloy of claim 1, wherein the Mg content is greater than 0.8%, by weight.
3. The aluminum alloy according to claim 1 or 2, comprising both the Ni and the Sn.
4. The aluminum alloy according to any one of claims 1 to 3 is used. Aluminum alloy wire.
5. The aluminum alloy wire according to claim 4, having a wire diameter of 3 mm or more and 15 mm or less.
6. After being subjected to solution treatment and aging treatment in sequence, the steel has a tensile strength of 450 MPa or more, The holding temperature of the solution treatment is a temperature selected from the range of 545° C. or more and 575° C. or less, and the holding time of the solution treatment is a time selected from the range of 30 minutes or more and 60 minutes or less, 6. The aluminum alloy wire according to claim 4 or 5, wherein a holding temperature of the aging treatment is selected from a range of 160° C. or higher and 180° C. or lower, and a holding time of the aging treatment is selected from a range of 5 hours or higher and 35 hours or lower.
7. The aluminum alloy wire according to claim 6, having a breaking elongation of 5% or more after the solution treatment and the aging treatment are sequentially performed.
8. An aluminum alloy wire as described in claim 6 or claim 7, having a 0.2% yield strength of 390 MPa or more after the solution treatment and the aging treatment are performed in sequence.
9. 1.0 mass% or more and 1.8 mass% or less of Si, 0.5% by mass or more and 1.2% by mass or less of Mg; 0.3% by mass or more and 0.8% by mass or less of Fe; 0.1% by mass or more and 0.4% by mass or less of Cu; 0.2% by mass or more and 0.5% by mass or less of Mn; 0% by mass or more and 0.3% by mass or less of Cr; Contains at least one of 0.005% by mass to 0.6% by mass of Ni and 0.005% by mass to 0.6% by mass of Sn, The balance is an aluminum alloy having a composition consisting of Al and unavoidable impurities, Having a tensile strength of 450 MPa or more; Aluminum alloy components.
10. The aluminum alloy structural member according to claim 9, which satisfies at least one of having a fracture elongation of 5% or more and a 0.2% yield strength of 390 MPa or more.
11. 1.0 mass% or more and 1.8 mass% or less of Si; 0.5% by mass or more and 1.2% by mass or less of Mg; 0.3% by mass or more and 0.8% by mass or less of Fe; 0.1% by mass or more and 0.4% by mass or less of Cu; 0.2% by mass or more and 0.5% by mass or less of Mn; 0% by mass or more and 0.3% by mass or less of Cr; Contains at least one of 0.005% by mass to 0.6% by mass of Ni and 0.005% by mass to 0.6% by mass of Sn, The balance is an aluminum alloy having a composition consisting of Al and unavoidable impurities, A tensile strength of 450 MPa or more; Elongation at break of 5% or more; Having a 0.2% yield strength of 390 MPa or more; bolt.
Citation Information
Patent Citations
6000 series aluminum alloy material with high natural aging stability, aluminum alloy plate and preparing method of aluminum alloy plate
CN104975209A
Aluminum alloy for cold forging
JP1996199276A
Al-mg-si series al alloy sheet excellent in toughness and bendability
JP2001262264A
High-strength aluminum alloy wire and rod material excellent in softening resistance and method of manufacturing the same
JP2010189750A
Aluminum alloy wire rod material for high-strength bolt having excellent formability, method for producing the same, high-strength flange bolt and method for producing the same
JP2011001602A